Skip to main content
Solve for x, y
Tick mark Image
Graph

Similar Problems from Web Search

Share

7x+9y=620,8x+4y=724
To solve a pair of equations using substitution, first solve one of the equations for one of the variables. Then substitute the result for that variable in the other equation.
7x+9y=620
Choose one of the equations and solve it for x by isolating x on the left hand side of the equal sign.
7x=-9y+620
Subtract 9y from both sides of the equation.
x=\frac{1}{7}\left(-9y+620\right)
Divide both sides by 7.
x=-\frac{9}{7}y+\frac{620}{7}
Multiply \frac{1}{7} times -9y+620.
8\left(-\frac{9}{7}y+\frac{620}{7}\right)+4y=724
Substitute \frac{-9y+620}{7} for x in the other equation, 8x+4y=724.
-\frac{72}{7}y+\frac{4960}{7}+4y=724
Multiply 8 times \frac{-9y+620}{7}.
-\frac{44}{7}y+\frac{4960}{7}=724
Add -\frac{72y}{7} to 4y.
-\frac{44}{7}y=\frac{108}{7}
Subtract \frac{4960}{7} from both sides of the equation.
y=-\frac{27}{11}
Divide both sides of the equation by -\frac{44}{7}, which is the same as multiplying both sides by the reciprocal of the fraction.
x=-\frac{9}{7}\left(-\frac{27}{11}\right)+\frac{620}{7}
Substitute -\frac{27}{11} for y in x=-\frac{9}{7}y+\frac{620}{7}. Because the resulting equation contains only one variable, you can solve for x directly.
x=\frac{243}{77}+\frac{620}{7}
Multiply -\frac{9}{7} times -\frac{27}{11} by multiplying numerator times numerator and denominator times denominator. Then reduce the fraction to lowest terms if possible.
x=\frac{1009}{11}
Add \frac{620}{7} to \frac{243}{77} by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.
x=\frac{1009}{11},y=-\frac{27}{11}
The system is now solved.
7x+9y=620,8x+4y=724
Put the equations in standard form and then use matrices to solve the system of equations.
\left(\begin{matrix}7&9\\8&4\end{matrix}\right)\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}620\\724\end{matrix}\right)
Write the equations in matrix form.
inverse(\left(\begin{matrix}7&9\\8&4\end{matrix}\right))\left(\begin{matrix}7&9\\8&4\end{matrix}\right)\left(\begin{matrix}x\\y\end{matrix}\right)=inverse(\left(\begin{matrix}7&9\\8&4\end{matrix}\right))\left(\begin{matrix}620\\724\end{matrix}\right)
Left multiply the equation by the inverse matrix of \left(\begin{matrix}7&9\\8&4\end{matrix}\right).
\left(\begin{matrix}1&0\\0&1\end{matrix}\right)\left(\begin{matrix}x\\y\end{matrix}\right)=inverse(\left(\begin{matrix}7&9\\8&4\end{matrix}\right))\left(\begin{matrix}620\\724\end{matrix}\right)
The product of a matrix and its inverse is the identity matrix.
\left(\begin{matrix}x\\y\end{matrix}\right)=inverse(\left(\begin{matrix}7&9\\8&4\end{matrix}\right))\left(\begin{matrix}620\\724\end{matrix}\right)
Multiply the matrices on the left hand side of the equal sign.
\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}\frac{4}{7\times 4-9\times 8}&-\frac{9}{7\times 4-9\times 8}\\-\frac{8}{7\times 4-9\times 8}&\frac{7}{7\times 4-9\times 8}\end{matrix}\right)\left(\begin{matrix}620\\724\end{matrix}\right)
For the 2\times 2 matrix \left(\begin{matrix}a&b\\c&d\end{matrix}\right), the inverse matrix is \left(\begin{matrix}\frac{d}{ad-bc}&\frac{-b}{ad-bc}\\\frac{-c}{ad-bc}&\frac{a}{ad-bc}\end{matrix}\right), so the matrix equation can be rewritten as a matrix multiplication problem.
\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}-\frac{1}{11}&\frac{9}{44}\\\frac{2}{11}&-\frac{7}{44}\end{matrix}\right)\left(\begin{matrix}620\\724\end{matrix}\right)
Do the arithmetic.
\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}-\frac{1}{11}\times 620+\frac{9}{44}\times 724\\\frac{2}{11}\times 620-\frac{7}{44}\times 724\end{matrix}\right)
Multiply the matrices.
\left(\begin{matrix}x\\y\end{matrix}\right)=\left(\begin{matrix}\frac{1009}{11}\\-\frac{27}{11}\end{matrix}\right)
Do the arithmetic.
x=\frac{1009}{11},y=-\frac{27}{11}
Extract the matrix elements x and y.
7x+9y=620,8x+4y=724
In order to solve by elimination, coefficients of one of the variables must be the same in both equations so that the variable will cancel out when one equation is subtracted from the other.
8\times 7x+8\times 9y=8\times 620,7\times 8x+7\times 4y=7\times 724
To make 7x and 8x equal, multiply all terms on each side of the first equation by 8 and all terms on each side of the second by 7.
56x+72y=4960,56x+28y=5068
Simplify.
56x-56x+72y-28y=4960-5068
Subtract 56x+28y=5068 from 56x+72y=4960 by subtracting like terms on each side of the equal sign.
72y-28y=4960-5068
Add 56x to -56x. Terms 56x and -56x cancel out, leaving an equation with only one variable that can be solved.
44y=4960-5068
Add 72y to -28y.
44y=-108
Add 4960 to -5068.
y=-\frac{27}{11}
Divide both sides by 44.
8x+4\left(-\frac{27}{11}\right)=724
Substitute -\frac{27}{11} for y in 8x+4y=724. Because the resulting equation contains only one variable, you can solve for x directly.
8x-\frac{108}{11}=724
Multiply 4 times -\frac{27}{11}.
8x=\frac{8072}{11}
Add \frac{108}{11} to both sides of the equation.
x=\frac{1009}{11}
Divide both sides by 8.
x=\frac{1009}{11},y=-\frac{27}{11}
The system is now solved.